Microfluidic amperometry with two symmetric Au microelectrodes under one-way and shuttle flow conditions. (20th February 2019) - Weng, Jui-Hong; Lai, Chih-Yu; Chen, Lin-Chi
Abstract: This paper studies the electrochemical measurements of ferricyanide redox reaction with two symmetric Au microelectrodes in microfluidics under one-way and shuttle flow conditions. An equal-molar Fe(CN)6 3− /Fe(CN)6 4− mixture was assayed with micro-fabricated Au electrodes placed inside a PDMS microfluidic channel by cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS) under a static or flow condition, respectively. It was found that the alignment and dimensions of microelectrodes played a crucial role in determining the electrochemical characteristics. Moreover, the redox characteristics were observed to be "tuneable" through microfluidic operations. Under the one-way flow mode, the CV response underwent a flow polarization effect that enhanced the downstream electrode reaction. Also, CV pattern transition from a typical wave shape to a sigmoidal curve was observed while increasing the flow rate for a microfluidic channel with a height ≤100 μm. In addition, steady-state CA responses instead of Cottrell-type currents were obtained owing to the convection-assisted mass transfer of ferricyanide. Under the shuttle flow mode, a liquid periodic motion effect was imposed on the CV measurement that resulted in oscillatory signals. By contrast, peak currents were produced in pairs periodically in the shuttle-mode CA, which were well-suited for redox quantitation and assessing the micro-mixing effect. Finally, both flow modes were proven effective to improve the detection sensitivity of microfluidic amperometry. Graphical abstract: Two-electrode cyclic voltammetry and amperometry on a chip tuned with one-way and shuttle microfluidics. Image 1